The Effectiveness of Dance E-Modules in Enhancing Conceptual Understanding among Elementary Students: A Study across School Accreditation Levels - Wecya Sugevin; Kusnadi; Sigit Wibowo (Universitas Pendidikan Ganesha, 2025)
Many elementary school teachers do not have adequate academic backgrounds in dance education, resulting in instruction that tends to focus on practice without strengthening conceptual understanding, which leads to low levels of students’ conceptual comprehension. This study aims to analyze and examine the effectiveness of using a dance e-module to improve elementary students’ conceptual understanding by considering differences in school accreditation levels. The study employed a quantitative approach with a pre experimental one group pretest posttest design. The participants consisted of 38 upper-grade elementary students selected through purposive sampling. Data were collected using a conceptual understanding test administered before and after the implementation of the e-module. The data were analyzed using normality tests, paired sample t-tests or Wilcoxon tests, and N-Gain analysis.The results revealed a statistically significant improvement (p < 0.05) after the use of the e-module. The level of effectiveness based on N-Gain ranged from low to moderate (0.23–0.50), indicating variations in improvement across schools. It can be concluded that the effectiveness of digital learning is influenced by institutional readiness and learning culture. The implication is that implementing e-modules in elementary arts education requires adequate digital literacy support and school readiness to ensure optimal and sustainable implementation.